Предмет: Алгебра,
автор: sifikialukr
Будь-ласка допоможіть!
Приложения:
Ответы
Автор ответа:
1
Объяснение:
3(a+c+x)-2(a+c-x)-(a-c+x)=2(c+2x)
3a+3c+3x-2a-2c+2x-a+c-x=2(c+2x)
(3a-2a-a)+(3c-2c+c)+(3x+2x-x)=2(c+2x)
0+2c+4x=2(c+2x)
2c+4x=2c+4x
Доказано
sifikialukr:
Дякую тобі велике! ☺️
Похожие вопросы
Предмет: Українська мова,
автор: annaochrimenko
Предмет: Алгебра,
автор: habenkonasta
Предмет: Литература,
автор: katerinamylianik
Предмет: Информатика,
автор: danilKashin2006
Предмет: ОБЖ,
автор: darina12345678935